Tomographic measurement of tidal current and associated 3-h oscillation in Bali Strait. (5th May 2020) - Hanifa, Aruni Dinan; Syamsudin, Fadli; Zhang, Chuanzheng; Mutsuda, Hidemi; Chen, Minmo; Zhu, Xiao-Hua; Kaneko, Arata; Taniguchi, Naokazu; Li, Guangming; Zhu, Ze-Nan; Gohda, Noriaki
Abstract: A coastal acoustic tomography experiment involving four acoustic stations was conducted from June 1–3, 2016 in the northern part of the Bali Strait. Range-average currents obtained along four transmission paths for a 30-h observation period were investigated in two-period bands: (a) > 6 h and (b) 10 min–6 h. The dominant phenomena for period bands (a) and (b) were semidiurnal tides with periods of approximately 12 h and internal modes with periods of approximately 3 h, respectively. The phase of the semidiurnal tidal currents was significantly deviated from a sea surface height-current relation expected for the progressive waves in the observation site. The 3-h oscillation had an amplitude comparable to that of the semidiurnal tidal current (with amplitudes of 1.5 ms −1 ) and was embedded in a semidiurnal envelope oscillation. In relation to the semidiurnal sea surface variations, the 3-h oscillation reached a peak at low water and diminished at high water. The velocity error of 0.07 ms −1 was estimated from the differential travel-time variations in the high-frequency band (10 min–1 h). The error was significantly smaller than the amplitudes of the semidiurnal tidal currents and the 3-h oscillation. Finally, it was suggested that the 3-h oscillation is an internal seiche synchronized with the semidiurnal tides. Highlights: Coastal acoustic tomography data with four separate ray paths are analyzed for two period bands (a) > 6 h and (b) 10 min-6 h. The 3-h oscillation is dominant in band (b) and has an amplitude comparable to the semidiurnal tidal current in band (a). The 3-h oscillation is embedded in semidiurnal envelope oscillation, which peaks at low water and diminishes at high water.